قواعد “التباین” فی المنهج القرآنی لمواجهة تهدیدات تریف الأخبار وتضلیل المعلومات (HOAX) فی العصر الرقمی (Digital Era) - Miftahur Rahman; Abqari Abqari (Alhadharah: Jurnal Ilmu Dakwah, 2020)
This study aims to describe the concept of "Tabayyun" by the Qur'an method in facing hoax news or false information the impact of the advancement of digital technology. This study uses a descriptive method. The question is how does the Qur'an provide views and solutions to face threats of that problem. The results of this study are six rules in the face of hoax news: Verification and balance, Stop sharing, Avoid negative prejudice, Read information critically and understand the text well, War on Hoax, Give literacy education to each individual Muslim in the use of modern media.